Binary temporal upconversion codes of Mn2+-activated nanoparticles for multilevel anti-counterfeiting. Issue 1 (December 2017) - Liu, Xiaowang; Wang, Yu; Li, Xiyan; Yi, Zhigao; Deng, Renren; Liang, Liangliang; Xie, Xiaoji; Loong, Daniel; Song, Shuyan; Fan, Dianyuan; All, Angelo; Zhang, Hongjie; et al.
Abstract Optical characteristics of luminescent materials, such as emission profile and lifetime, play an important role in their applications in optical data storage, document security, diagnostics, and therapeutics. Lanthanide-doped upconversion nanoparticles are particularly suitable for such applications due to their inherent optical properties, including large anti-Stokes shift, distinguishable spectroscopic fingerprint, and long luminescence lifetime. However, conventional upconversion nanoparticles have a limited capacity for information storage or complexity to prevent counterfeiting. Here, we demonstrate that integration of long-lived Mn2+ upconversion emission and relatively short-lived lanthanide upconversion emission in a particulate platform allows the generation of binary temporal codes for efficient data encoding. Precise control of the particle's structure allows the excitation feasible both under 980 and 808 nm irradiation. We find that the as-prepared Mn2+ -doped nanoparticles are especially useful for multilevel anti-counterfeiting with high-throughput rate of authentication and without the need for complex time-gated decoding instrumentation. Luminescent materials that are capable of binary temporal coding are desirable for multilevel anti-counterfeiting. Here, the authors engineer nanoparticles that produce binary color codes on different timescales by combining the long-lived luminescence of Mn2+ with the relatively short-lived emission of lanthanides.